A Rapid Prediction of Suppressed Vibration in Composite Bridges Equipped with Constrained Layer Damping - Quanmin Liu; Weiwang Fu; Lizhong Song; Kui Gao; Peipei Xu (Buildings)
The vibration characteristics of a composite bridge with constrained layer damping (CLD) were investigated using the wave and finite element method (WFEM), and the effects of the material and geometrical parameters of the CLD on the vibration reduction in the bridge were analyzed. Firstly, a numerical model for the dynamic response of a composite steel–concrete bridge using WFEM. The calculated acceleration of the bridge under the wheel–rail force obtained using this model was in good agreement with that obtained using the conventional finite element method and field measurements. Second, a segment model of the bridge with a CLD was established. The equation of motion based on the WFEM was solved to determine the dynamic response of the bridge induced by running trains. Finally, the effects of the covering area and CLD parameters on the vibration mitigation of steel–concrete bridges were analyzed. The results show that a reduction of 5–10 dB of the acceleration level of steel members in the full frequency range can be achieved by installing the CLD. A lower shear modulus of the viscoelastic core is beneficial for low-frequency vibration reduction in the bridge. However, a higher shear modulus of the damping layer is required for vibration mitigation in the high-frequency range. The vibration reduction in the composite bridge was more sensitive to the thickness of the constraining layer than to that of the damping layer.